2009
DOI: 10.1080/09540120802001697
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and depression as mediators of the relationship between pain and antiretroviral adherence

Abstract: The goals of this study were to examine the association between pain and antiretroviral adherence, and to estimate the mediating effect of adherence self-efficacy and depression symptom severity. Surveys using audio computer-assisted self-interview were conducted among 70 HIV-infected current and former drug users enrolled in a methadone program. We assessed antiretroviral adherence and adherence self-efficacy using questions from the Adult Clinical Trials Group survey. We considered participants adherent if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…The mean adherence self-efficacy score of 6.45 out of a possible 10 compares well with a previous study by Berg et al 33 whereby the mean adherence self-efficacy was a moderate 1.81 on a scale of 0-3 in a study that sought to ascertain if self-efficacy and depression mediated the relationship between pain and adherence to ART in HIV-infected current and former drug users enrolled in a methadone programme in the USA. Within the context of adherence self-efficacy with respect to ART, patients who demonstrated sound confidence in carrying out the tasks were shown to adhere well to the treatment, and those with low …”
Section: Discussionsupporting
confidence: 70%
“…The mean adherence self-efficacy score of 6.45 out of a possible 10 compares well with a previous study by Berg et al 33 whereby the mean adherence self-efficacy was a moderate 1.81 on a scale of 0-3 in a study that sought to ascertain if self-efficacy and depression mediated the relationship between pain and adherence to ART in HIV-infected current and former drug users enrolled in a methadone programme in the USA. Within the context of adherence self-efficacy with respect to ART, patients who demonstrated sound confidence in carrying out the tasks were shown to adhere well to the treatment, and those with low …”
Section: Discussionsupporting
confidence: 70%
“…Unlike as in some prior studies that reported associations between pain and adherence to HIV medications [36, 40], pain was not associated with ART use or HIV control. In the fully adjusted models, the only factors that were independently associated with mortality were HCV co-infection and low CD4 cell count, which are established risk factors for mortality among persons with HIV and alcohol use disorders [41].…”
Section: Discussioncontrasting
confidence: 88%
“…Although elevated with respect to the general population, this finding is in line with prior research on HIV-positive patients, which has gauged pain prevalence to be between 40% and 80%. [1][2][3][4] Our data confirm that pain is an exceedingly common co-morbid health condition among HIV-positive individuals, including the non-elderly and those treated in an era of ARVs with lower side effect profiles. Although this study did not gather information on pain intensity or duration, prescribed pharmacotherapy to treat pain was modest, with 41.5% of those endorsing pain being untreated.…”
Section: Discussionsupporting
confidence: 68%
“…10 Despite these challenges, balanced and appropriate pain management among vulnerable HIV patients is critical to both individual and public health. 7 A small but emerging body of literature suggests that pain experience among HIV-positive patients is associated with poor ARV adherence and reduced attendance at HIV-related care visits, 2,3,14 both of which are key behavioral components of disease management to achieve viral suppression and prevent onward transmission. 15,16 Although a handful of other studies has shown no link between pain and ARV treatment adherence, 1,13 the dearth of research on this topic precludes consensus.…”
mentioning
confidence: 99%
See 1 more Smart Citation